1993
DOI: 10.1056/nejm199304013281303
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Drug Therapy for Hypertension in Men -- A Comparison of Six Antihypertensive Agents with Placebo

Abstract: Among men, race and age have an important effect on the response to single-drug therapy for hypertension. In addition to cost and quality of life, these factors should be considered in the initial choice of a drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
317
0
8

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,085 publications
(337 citation statements)
references
References 16 publications
12
317
0
8
Order By: Relevance
“…The data of Materson et al 58 on elderly patients showed that the best antihypertensive response occurred with diltiazem, followed by hydrochlorothiazide, clonidine and prazosin. Atenolol was only slightly better than placebo and captopril was worse than placebo.…”
Section: Elderly Black Hypertensive Patientsmentioning
confidence: 98%
See 2 more Smart Citations
“…The data of Materson et al 58 on elderly patients showed that the best antihypertensive response occurred with diltiazem, followed by hydrochlorothiazide, clonidine and prazosin. Atenolol was only slightly better than placebo and captopril was worse than placebo.…”
Section: Elderly Black Hypertensive Patientsmentioning
confidence: 98%
“…The authors conclude that, as yet, no ideal monotherapy exists for hypertension in black diabetic patients. 57 Materson et al 58 found in a randomised doubleblind study of 1292 men with a diastolic BP of 95-109 mm Hg that diltiazem ranked first for younger whites and atenolol for older whites. The patients were randomised after a placebo washout period to receive placebo or one of the six drugs: hydrochlorothiazide (12.5-50 mg per day), atenolol (25-100 mg per day), captopril (25-100 mg per day), clonidine (0.2-0.6 mg per day), a sustained-release preparation of diltiazem (120-360 mg per day), or prazosin (4 -20 mg per day).…”
Section: Calcium Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This behaviour probably contributes substantially to the low overall rate of hypertension control in the community, since a significant proportion of patients do not attain target blood pressure on a single agent. 4,6,8,9 Well-tolerated fixed-dose combination therapies are becoming available that should facilitate the attainment of blood pressure targets early in the treatment process.…”
Section: Introductionmentioning
confidence: 99%
“…However with these exceptions, despite the increasing global problem of hypertension, most trial data hail from the developed Western world and no trials have been carried out purely in the developing world in, for example, black or south Asian hypertensive patients. Given ethnic dif-ferences in blood pressure responses for various antihypertensive agents, 48 the results of such trials may have major implications for the majority of the world's hypertensives who hail from such countries. Meanwhile the large Afro-Caribbean component randomised in the ALLHAT trial will provide some evidence regarding this sub-group, albeit in a Westernised setting.…”
Section: Other Trials Neededmentioning
confidence: 99%